2003
DOI: 10.1590/s0103-90162003000200008
|View full text |Cite
|
Sign up to set email alerts
|

Tillering does not interfere on white oat grain yield response to plant density

Abstract: Plant density is one of the cropping practices that has the largest impact on individual plant growth. This work was conducted to evaluate the response of white oat (Avena sativa) cultivars with contrasting tillering patterns to variations in plant density. Two field experiments were carried out in Lages, SC, Brazil, during the 1998 and 1999 growing seasons. A split plot experimental design was used. Four oat cultivars were tested in the main plots: UFRGS 14, UFRGS 18, UPF 16 and UPF 17 using five plant densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…In wheat, Zagonel et al (2002) showed that higher density of plants may favor the increase of grainproductivity, to the point of identifying genotypes that were responsive to the increase of the population. Almeida et al (2003)have already observed, in oat obsolete cultivars of middle and late cycle, amplitude of seeds density adjustedfrom 50 to 500 plants m -2 . The increment of the sowing density inearly cycle wheat cultivars, mainly of lower expression of tillering, presented benefits in the increase of sowing density on grain productivity (Silveira et al, 2010).…”
Section: Resultsmentioning
confidence: 80%
“…In wheat, Zagonel et al (2002) showed that higher density of plants may favor the increase of grainproductivity, to the point of identifying genotypes that were responsive to the increase of the population. Almeida et al (2003)have already observed, in oat obsolete cultivars of middle and late cycle, amplitude of seeds density adjustedfrom 50 to 500 plants m -2 . The increment of the sowing density inearly cycle wheat cultivars, mainly of lower expression of tillering, presented benefits in the increase of sowing density on grain productivity (Silveira et al, 2010).…”
Section: Resultsmentioning
confidence: 80%
“…However, the eucalyptus tiller-suppression was strong near the trees, suggesting that in addition to nitrogen, other agronomic practices must be used, such as a higher seeding rate (e.g., PELTONEN-SAINIO et al, 1995;ALMEIDA et al, 2003) combined or not with other plant arrangements, to the community took on uniculm growth habit. GILL et al (2009) observed a declining trend in the tiller number of wheat varieties, which increase in age from 4 to 6 years old in a poplar plantation.…”
Section: Resultsmentioning
confidence: 99%
“…Results of this research reinforce the idea that the chances of tillers to contribute to grain yield are reduced under stressful conditions. Considering that there must be a synchronism between tillers and main stem development, so that tillers can substantially contribute to grain yield (Wobeto, 1994, Merotto Jr., 1995, Almeida et al (2002;2003) raised the question about the real importance of tillering to improve wheat performance under the environmental conditions prevailing in the growing regions of Southern Brazil. In this work, treatments were chosen aiming to simulate stresses commonly found in wheat fields, and to evaluate their influence on the tillering process.…”
Section: Resultsmentioning
confidence: 99%